The hill [compact disc] - Lewis, Aaron (The Valory Music Co., 2024)
Aaron Lewis grew up in Springfield, Vermont, listening to his grandparents' Country 8-track tapes. Those roots inspired the multi-platinum Staind founder to return to his origins for the No. One Billboard Country Album debuts Town Line and Sinner, as well as Billboard's No. One Hot Country Song debut "Am I The Only One." Lewis has put a traditionalist brand on his outlier Country, and with his new album, the fifteen million-selling workingman's star offers his most personal and unplugged collection to date.